2016
DOI: 10.3354/aei00198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water spinach Ipomoea aquatica cultivation on water quality and performance of Chinese soft-shelled turtle Pelodiscus sinensis pond culture

Abstract: The Chinese soft-shelled turtle Pelodiscus sinensis is a highly valued freshwater species cultured in China. A 122 d experiment was conducted to assess the effects of water spinach Ipomoea aquatica cultivation in floating beds on water quality, and growth performance and economic return of P. sinensis cultured in ponds. Two treatments, each in triplicate, with and without I. aquatica cultivation were designed. Results showed that the levels of total ammonia nitrogen (TAN), total nitrogen (TN), total phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…and water spinach ( Ipomoea aquatica Forsk), have been reported to be efficient at removing nutrients from eutrophic water (Tripathi & Upadhyay, ; Zhang et al, ). The reduction in nitrogen and phosphorus compositions in the present study were likely the result of nutrient accumulation in plant tissues and periphyton growth on plant roots and stems (Li et al, ; Wu, Xia, Yu, Shabbir, & Kerr, ).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…and water spinach ( Ipomoea aquatica Forsk), have been reported to be efficient at removing nutrients from eutrophic water (Tripathi & Upadhyay, ; Zhang et al, ). The reduction in nitrogen and phosphorus compositions in the present study were likely the result of nutrient accumulation in plant tissues and periphyton growth on plant roots and stems (Li et al, ; Wu, Xia, Yu, Shabbir, & Kerr, ).…”
Section: Discussionmentioning
confidence: 59%
“…Water quality management is considered essential for ensuring high production and quality in aquaculture systems (Li et al, ; Love et al, ; Mohanty, Ambast, Panigrahi, Thakur, & Mandal, ) and for water conservation (Mohanty, Ambast, Panigrahi, & Mandal, ; Zhang, Achal, Xu, & Xiang, ). The use of aquatic macrophytes to remove nutrients from aquaculture effluents has been reported as a promising phytoremediation method (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It plays a role in promoting the cycling of carbon and nitrogen in water environments, improving water quality. HgcI_clade is considered one of the persistent microorganisms in global oligotrophic aquatic ecosystems, characterized by its high and stable abundance (Huang et al, 2020; Li et al, 2016). Previous studies have shown that HgcI_clade is a dominant bacterial group in water environments of rice paddies under different fertilization modes and fish-vegetable co-culture systems (Newton et al, 2011; Ruprecht et al, 2021), which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%